Halal Certification: The Gap between Administrative Compliance and Consumer Protection - Nurul Fibrianti; R. Benny Riyanto; Ubaedul Mustofa; Shopia Clara Beauty Kusumawardhani; Anik Novita (Journal of Indonesian Legal Studies, 2026)
Halal certification in Indonesia is regulated under Law No. 33 of 2014 on Halal Product Guarantee (Jaminan Produk Halal, JPH). Initially voluntary, certification is now mandatory for all products circulated, marketed, and traded in Indonesia. This study analyzes Indonesia's halal certification policy from a consumer protection law perspective. Although current policies emphasize increasing the number of halal-certified businesses, oversight of halal production through the self-declaration mechanism relies largely on the honesty of business actors, creating risks of Sharia compliance violations and undermining consumers' spiritual rights. The research employs a normative-empirical legal approach. Secondary data were obtained from the JPH Law, its implementing regulations, and the Consumer Protection Law, while primary data were collected through field research involving business actors. The findings show that despite mandatory certification requirements, compliance remains low and law enforcement is weak. The study contributes by examining legal harmonization and enforcement effectiveness in safeguarding Muslim consumers' right to halal products. From a consumer protection perspective, the current halal certification regime does not fully meet the standards required under the Consumer Protection Law. The self-declaration mechanism weakens consumer protection by reducing regulatory oversight and prioritizing ease of doing business over rigorous certification. Moreover, the absence of strict liability provisions and compensation for immaterial or spiritual losses indicates that halal regulation is still treated primarily as an economic instrument rather than a mechanism for protecting fundamental consumer rights. At the UMKM level, implementation often reflects pseudo-compliance, with halal labels used mainly as marketing tools rather than evidence of genuine Sharia compliance.